2010
DOI: 10.1158/1078-0432.ccr-09-3239
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Activating EGFR Mutations in Non–Small Cell Lung Cancer Using Mutation-Specific Antibodies for Immunohistochemical Analysis

Abstract: Purpose: Therapeutic responses of non-small cell lung carcinoma (NSCLC) to epidermal growth factor receptor (EGFR)-targeted drugs, such as gefitinib and erlotinib, are closely associated with activating EGFR mutations. The most common mutations are delE746-A750 in exon 19 and L858R in exon 21, accounting for ∼90% of all EGFR mutations. Recently, EGFR mutation-specific antibodies were developed and did well in immunohistochemical analysis, giving a sensitivity of ∼90%. We have investigated whether this method d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 21 publications
7
92
1
2
Order By: Relevance
“…[14][15][16][17][18][19][20][21][22] All these studies used the same mutation-specific antibodies from Cell Signaling Technology and the methods were comparable. Simonetti et al found specificity of 100% for both antibodies in 78 unselected Caucasian patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[14][15][16][17][18][19][20][21][22] All these studies used the same mutation-specific antibodies from Cell Signaling Technology and the methods were comparable. Simonetti et al found specificity of 100% for both antibodies in 78 unselected Caucasian patients.…”
Section: Discussionmentioning
confidence: 99%
“…21 Previous studies using the mutation-specific antibodies from Cell Signaling Technology have found sensitivity ranging from 23 to 80% for exon19 deletions and 36 to 100% for exon21 mutations. [14][15][16][17][18][19][20][21][22] These studies used different scores for intensity and cutoff point for positivity making comparisons between the individual studies difficult, and standardization is warranted. 23 No gold standard method is approved for detecting EGFR mutations in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity of the mutation-specific antibodies, although high, is not 100%, and after the initial reports, more recent studies have calculated the sensitivity to be as low as 80%. 37,38 In their cohort, Kitamura et al 39 were able to detect only 47% of mutations using the mutationspecific antibodies, probably because of the high frequency of nonclassic deletions in that particular cohort.…”
Section: Discussionmentioning
confidence: 99%